2018
DOI: 10.30773/pi.2018.10.21.1
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Korean Version of the Biological Rhythms Interview of Assessment in Neuropsychiatry

Abstract: ObjectiveThe Biological Rhythms Interview of Assessment in Neuropsychiatry (BRIAN) is a scale used to clinically evaluate disturbances in biological rhythm. In this study, we aimed to examine the reliability and validity of the Korean version of the BRIAN (K-BRIAN) in a Korean population. MethodsA total of 181 participants, including 141 outpatients with bipolar disorder (BD; type I, 62; type II, 79) and 40 controls, were recruited. Construct validity was tested by comparing the mean K-BRIAN scores of the BD p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 37 publications
2
20
0
Order By: Relevance
“…Moreover, the mean total BRIAN score of bipolar II disorder in previous studies conducted in Korea [27,33] was close to that of the eMDD group in our study. However, there is no cut-off BRIAN score distinguishing bipolar disorder from MDD, and most individuals in the eMDD group demonstrated a significant amount of biological rhythmic disturbances similar to those with bipolar II disorder.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Moreover, the mean total BRIAN score of bipolar II disorder in previous studies conducted in Korea [27,33] was close to that of the eMDD group in our study. However, there is no cut-off BRIAN score distinguishing bipolar disorder from MDD, and most individuals in the eMDD group demonstrated a significant amount of biological rhythmic disturbances similar to those with bipolar II disorder.…”
Section: Discussionsupporting
confidence: 85%
“…These patients were recruited from the psychiatry outpatient clinic of the Korea University Hospital. The HC group comprised 40 individuals recruited from the general population of young adults [27]. All study participants were informed in detail about the purpose and procedures of the study prior to signing an informed consent form.…”
Section: Participantsmentioning
confidence: 99%
“…[23], which classified 138 subjects with BD I, 170 subjects with BD II, and 159 subjects with MDD. 40 control subjects were recruited by matching gender and age from the general population of young adults at Korea University Anam Hospital [21].…”
Section: Methodsmentioning
confidence: 99%
“…BRIAN consists of 21 items divided into five main areas, related to circadian rhythm disturbance in psychiatric subjects. These five domains are sleep, activities, social-rhythm, eating-pattern, and predominant-rhythm [20], and BRIAN’s validity and reliability have been confirmed for Korean population [21].…”
Section: Introductionmentioning
confidence: 99%
“…It also suggested that and subjective measures (BRIAN) provide extensive evidence of sleep and biological rhythm system disruptions in mental disorders [44]. Also, the BRIAN appears to be a feasible tool to evaluate all domain of biological rhythms, due to the other scales that only indirectly measure biological rhythm by testing seasonality or chronotype or subjective quality of sleep [45].…”
Section: Discussionmentioning
confidence: 99%